An analysis of the teaching performance of teachers of elementary schools in Kupang - Lukas Manu; Johanis N. Kallau; Paulus Taek; Fredrik Abia Kande (Graduate School, Universitas Negeri Yogyakarta, 2020)
This research aims to reveal the differences between the performance of bachelor degree holder teachers and that of non-degree holder teachers of elementary schools in Kupang. It applies the survey method. The data were collected using a questionnaire. The questionnaire's validity was measured using the Product Moment Correlation formula, and its reliability was measured using the Alfa Cronbach formula. The data analysis used the non-parametric Mann-Whitney test with the help of the SPSS Program. The result of the study shows that there is a significant average difference between the teaching performance of bachelor degree holder teachers and that of non-degree holder teachers of elementary schools in Kupang. There is a significant average difference between bachelor degree holder teachers' personality competence and that of non-degree holder teachers. There is a significant average difference between the paedagogic competence of bachelor degree holder teachers and non-degree holder teachers. There is a significant average difference between bachelor degree holder teachers' social competence and that of non-degree holder teachers. Therefore, it is suggested that non-degree holder teachers keep improving their academic qualification and work performance through varieties of self-development efforts.